Chronic obstructive pulmonary disease among residents of an historically industrialised area. Issue 10 (28th June 2012) - Darby, Anthony C; Waterhouse, Judith C; Stevens, Vivien; Billings, Clare G; Billings, Catherine G; Burton, Clare M; Young, Charlotte; Wight, Jeremy; Blanc, Paul D; Fishwick, David
Abstract : Objective: To assess the contribution of workplace exposures to chronic obstructive pulmonary disease (COPD) risk in a community with a heavy burden of past industrial employment. Methods: A random population sample of Sheffield, UK residents aged over 55 years (n=4000), enriched with a hospital-based supplemental sample (n=209), was approached for study. A comprehensive self-completed questionnaire elicited physician-made diagnoses, current symptoms, and past workplace exposures. The latter were defined in three ways: self-reported exposure to vapours, gases, dusts and fumes (VGDF); response to a specific exposure checklist; and through a job exposure matrix (JEM) assigning exposure risk likelihood based on job history independent of respondent-reported exposure. A subset of the study group underwent lung function testing. Population attributable risk fractions (PAR%), adjusted for age, sex and smoking, were calculated for association between workplace exposure and COPD. Results: 2001 (50%) questionnaires were returned from the general population sample and 60 (29%) by the hospital supplement. Among 1754 with complete occupational data, any past occupational exposure to VGDF carried an adjusted excess risk for report of a physician's diagnosis of COPD, emphysema, or chronic bronchitis (ORs 3.9; 95% CI 2.7 to 5.8), with a corresponding PAR% value of 58.7% (95% CI 45.6% to 68.7%). The PAR% estimate based on JEM exposure was 31%. From within the subgroup of 571 that underwent lung function testing, VGDF exposure was associated with a PAR% of 20.0% (95% CI −7.2 to 40.3%) for Global initiative for chronic Obstructive Lung Disease (GOLD) 1 (or greater) level of COPD. Conclusion: This heavy industrial community-based population study has confirmed significant associations between reported COPD and both generic VGDF and JEM-defined exposures. This study supports the predominantly international evidence-based notion that workplace conditions are important when considering the current and future respiratory health of the workforce.